2021
DOI: 10.1108/jcre-03-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of healthy workplaces on employee satisfaction, productivity and costs

Abstract: Purpose This paper aims to explore the added value of healthy workplaces for employees and organizations, in particular regarding employee satisfaction, labour productivity and facility cost. Design/methodology/approach The paper is based on a narrative review of journal papers and other sources covering the fields of building research, corporate real estate management, facilities management, environmental psychology and ergonomics. Findings The review supports the assumption of positive impacts of appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 59 publications
1
23
0
2
Order By: Relevance
“…In terms of job satisfaction, the majority of respondents indicated their need to work in an aesthetically pleasing workplace (Bjerke et al , 2007; Molahosseini et al , 2020) to feel satisfied in their work. This belief has also been shown in other studies including Van der Voordt and Jensen (2023) that highlighted how appropriate building characteristics can positively impact people’s health, satisfaction and productivity. Our respondents also believed an aesthetically pleasing work environment enhanced both their productivity and satisfaction.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In terms of job satisfaction, the majority of respondents indicated their need to work in an aesthetically pleasing workplace (Bjerke et al , 2007; Molahosseini et al , 2020) to feel satisfied in their work. This belief has also been shown in other studies including Van der Voordt and Jensen (2023) that highlighted how appropriate building characteristics can positively impact people’s health, satisfaction and productivity. Our respondents also believed an aesthetically pleasing work environment enhanced both their productivity and satisfaction.…”
Section: Discussionsupporting
confidence: 64%
“…Kellert et al (2011) mention that much architectural work now considers how natural lighting and plants will feature in spaces. Voordt and Jensen (2023) showed that healthy workplaces have a positive impact on end-user satisfaction and employee productivity as well.…”
Section: Rq2mentioning
confidence: 99%
“…This finding is in line with prior research, e.g., refs. [62,63] which claimed that ergonomics increases work engagement. Employees obtain a sense of ownership and control over their work environment when they have the chance to contribute to the design of their workplaces and equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing ergonomic interventions demonstrates that the organization values the health and comfort of its employees, which can result in increased job satisfaction and a sense of being valued. Satisfied employees are more likely to be engaged, motivated, and willing to invest discretionary effort into their work tasks [62,63].…”
Section: The Relationship Between Ergonomics and Work Engagementmentioning
confidence: 99%
“…Social sustainability is challenging to describe in a way that is both understandable and meaningful to businesses and the various external stakeholders in the government and the society with whom they engage [13]. Although the review by Voordt and Jensen [14] shows that appropriate building characteristics have been recognized for their positive effects on health, satisfaction, and productivity, the correlations between these impacts remain understudied. Therefore, the way through which the work environment enables productivity is impactful on satisfaction, productivity, and quality of life [15].…”
Section: Literature Reviewmentioning
confidence: 99%